1997
DOI: 10.1258/0956462971919985
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and hospice resource use of HIV-positive patients in Edinburgh

Abstract: A prospective study of health service and hospice resource utilization (average length of stay or ALOS, discharge rate, bed day use, outpatient consultation) analysed with reference to gender, risk activity, immunological and clinical staging (1987 definition of AIDS) for the financial year 1992-93 was undertaken at the Regional Infectious Disease Unit (RIDU), City Hospital, Edinburgh, Scotland where 72% of 513 patients were infected via injection drug use. Not surprising therefore overall, drug users were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example one study among French IDUS found that approximately 50% of patients prescribed HAART take less than 80% of the treatment [152] while many IDUs remain reluctant to start HAART [158,159]. Consequently, IDUs with adherence problems have worse health outcomes than other PLWHA on HAART [152,160,161].…”
Section: Access To Antiretroviral Therapymentioning
confidence: 99%
“…For example one study among French IDUS found that approximately 50% of patients prescribed HAART take less than 80% of the treatment [152] while many IDUs remain reluctant to start HAART [158,159]. Consequently, IDUs with adherence problems have worse health outcomes than other PLWHA on HAART [152,160,161].…”
Section: Access To Antiretroviral Therapymentioning
confidence: 99%
“…In a prospective study by the Regional Infectious Disease Unit in Scotland, health service and hospice use by HIVinfected individuals was evaluated for 1992±93 12 . Most of the 513 patients (72%) had been infected through injection drug use.…”
Section: Palliative Care For Aids In the Ukmentioning
confidence: 99%
“…However pre-AIDS bed day use in Edinburgh, predominantly as a result of injection drug users, was greater than in London or Shef® eld; 460 days per 100 person years in Edinburgh compared to 271 in London and 209 in Shef® eld 36± 39 . On closer examination of the pre-AIDS discharge rate in Edinburgh revealed that it was 51 per 100 person years for drug users compared to 13 per 100 person years in homosexuals and bisexuals 39 . This increased pre-AIDS morbidity seems to be characteristic of IDUrelated HIV and much of it is related to problems with bacterial infections.…”
Section: Pre-aidsmentioning
confidence: 99%